Effectiveness of pre-employment card policy on employment transition during covid-19: evidence from Indonesian dual labor market - Gunawan, Beni Teguh; Apriyanto, El Bram; Hennigusnia, Hennigusnia; Suryono, Ivan Lilin; Kurniawati, Ardhian (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The COVID-19 pandemic has significantly disrupted employment markets globally and nationally, posing unique challenges to Indonesia’s labor force. In response, the Indonesian government launched the Pre-Employment Card (PEC) as part of the National Economic Recovery (PEN) initiative to mitigate rising unemployment and facilitate transitions to sustainable employment.  This study examines the effectiveness of Indonesia’s Pre-Employment Card (PEC) policy in facilitating employment transitions during the COVID-19 pandemic. The effectiveness of the PEC policy is measured through key indicators such as labor absorption rates, reduction in unemployment, and the likelihood of securing formal employment over informal alternatives. This study introduces a novel perspective by employing a dual labor market approach, which highlights the distinct roles and interactions of formal and informal sectors in Indonesia’s labor market. Specifically, it examines how the presence of informality affects job transitions and the effectiveness of the Pre-Employment Card (PEC) policy in facilitating movement toward formal sector employment.  To analyze employment transitions, this research employs a multinomial logit model, selected for its ability to estimate the probability of multiple, categorical employment outcomes, making it especially suitable for evaluating the diverse pathways individuals might take from unemployment to formal or informal employment, and from informal to formal sectors. The findings reveal that the PEC policy significantly increases the likelihood of unemployed individuals securing formal sector jobs rather than informal ones, with participants who completed the initial PEC training showing a 30% higher probability of transitioning to formal employment compared to those without PEC support. Additionally, the policy supports transitions within the labor market by facilitating movement from the informal to the formal sector, with an observed 25% increase in formal employment uptake among informal workers participating in PEC. These results underscore the PEC policy’s effectiveness in promoting formal employment pathways, contributing to workforce stabilization amid economic recovery efforts.